Diseño de una ruta agroturística para el fomento del turismo rural en el cantón Chone - Chasing Chávez, Jarely Michelle (2023)
The purpose of this work was to design an agrotourism route that promotes the development of rural tourism in Chone canton. To this end, the research was carried out in three stages. The first stage consisted in the characterization of the territory to identify the agrotourism potential; in the second, the tourism system was analyzed as a baseline for the structuring of an agrotourism route; and, in the third stage, the elements for the articulation of the aforementioned were defined, framed in the strengthening of the rural tourism offer in Chone canton. The findings demonstrated that the study area has the potential to develop agrotourism products; however, the human settlements in these rural territories suffer from serious limitations in terms of basic and complementary services, as well as the preponderance of a tourist offer limited to spas, seasonal demand and local visitors. However, the identification of farms with tourist benefits allowed the development of a route focused on the use of Chone’s agro-productive resources, presenting a differentiated proposal oriented towards agrotourism and recreation within rural areas. In conclusion, Chone canton presents ideal natural, scenic and environmental conditions for the development of an agrotourism route; on the other hand, there are clear limitations in the socio-cultural, economic, infrastructure and governance dimensions for tourism, which must be overcome in order to guarantee the success of the route within the market.